2020
DOI: 10.1007/s00737-020-01055-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors promoting resilience during the menopausal transition

Abstract: Despite significant biological, psychological, and social challenges in the perimenopause, most women report an overall positive well-being and appear to be resilient to potentially negative effects of this life phase. The objective of this study was to detect psychosocial variables which contribute to resilience in a sample of perimenopausal women. A total of 135 healthy perimenopausal women aged 40–56 years completed a battery of validated psychosocial questionnaires including variables related to resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
0
3
1
1
Order By: Relevance
“…According to the different pressures faced by women during the pandemic, the adaptation methods came to be different. The researchers found their findings regarding coping strategies differ from some other studies that as [29], [30], [31]. The present study revealed significant relations among participants' coping measures to face their menopausal complaints during the pandemic.…”
Section: Discussioncontrasting
confidence: 82%
“…According to the different pressures faced by women during the pandemic, the adaptation methods came to be different. The researchers found their findings regarding coping strategies differ from some other studies that as [29], [30], [31]. The present study revealed significant relations among participants' coping measures to face their menopausal complaints during the pandemic.…”
Section: Discussioncontrasting
confidence: 82%
“…Estilo de vida relacionado a la autoactualización, desde la teoría de Nola Pender, debe comprenderse como aquello a lo que se desea llegar con relación al desarrollo del potencial humano, obtención de logros (29) . Este aspecto, las mujeres participantes en el estudio, se observaron con una fortaleza en cuanto a los aspectos relacionados con aceptarse y quererse a sí mismas, optimistas, satisfacción con el ambiente personal, situación que coincide con otros estudios similares, estos resultados coinciden con un estudio realizado en un grupo de mujeres peruanas donde se encontró que en su mayoría presentan una autoestima alta e igualmente se encontró en otro estudio que las mujeres optimistas, con estabilidad emocional, regulación emocional, autocompasión y autoestima presentan mejor salud mental para enfrentar este proceso de transición (30,31) .…”
Section: Discussionunclassified
“…The results of studies using the same tool to assess women’s self-esteem show that most women in Haiti over 45 years old had low self-esteem [ 24 ]. In Spain, about 35.6% of women reported low self-esteem [ 20 ], and in Switzerland, most menopausal women had moderate self-esteem [ 25 ]. Taken together, there are many unanswered questions regarding self-esteem in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%